Information and Communication Technologies Adoption in Small Firms (Management in Perspective, 2020)
Information and Communication Technologies (ICTs) can provide a set of benefits to companies, such as efficiency gains in managerial activities, cost reduction and faster communication with consumers. The ICT literature has studies showing the positive impact that the IT adoption can generate on the company’s performance. ICT benefits are also extensive to small business, but their particular characteristics do not always support their adoption by these enterprises, especially when they are enterprises situated in developing countries. In this context, the aim of this paper was to identify how the ICT adoption and the ICT intention of use are in Brazilian small firms. We have used a case study and we have collected data from four enterprises. In order to collect the data, we used qualitative interviews, direct observation and documental analysis. The main results have shown that the owner’s characteristics, the understanding of the ICT benefits, the ICT complexity and the costs/time related to training people are factors associated with the ICT adoption and intention of use. Based on the literature review and on the empirical evidence, we have found that there is an opportunity cost related to postponing the decision of the ICT investments. We also discuss the role of geographical localization of the enterprises, which can contribute to the ICT literature.